Evidence for a vibrational phase-dependent isotope effect on the photochemistry of vision - Schnedermann, C; Yang, X; Liebel, M; Spillane, K; Lugtenburg, J; Fernández, I; Valentini, A; Schapiro, I; Olivucci, M; Kukura, P; Mathies, R (Nature Publishing Group, 2018)
Vibronic coupling is key to efficient energy flow in molecular systems and a critical component of most mechanisms invoking quantum effects in biological processes. Despite increasing evidence for coherent coupling of electronic states being mediated by vibrational motion, it is not clear how and to what degree properties associated with vibrational coherence such as phase and coupling of atomic motion can impact the efficiency of light-induced processes under natural, incoherent illumination. Here, we show that deuteration of the H11-C11=C12-H12 double-bond of the 11-cis retinal chromophore in the visual pigment rhodopsin significantly and unexpectedly alters the photoisomerization yield while inducing smaller changes in the ultrafast isomerization dynamics assignable to known isotope effects. Combination of these results with non-adiabatic molecular dynamics simulations reveals a vibrational phase-dependent isotope effect that we suggest is an intrinsic attribute of vibronically coherent photochemical processes.